Adaptation of Schmallenberg virus to continuous cell cultures - S. V. Kononova; A. A. Nesterov; V. V. Dumova; B. L. Manin; A. V. Kononov; Yu. Yu. Babin; O. G. Gubenko (Ветеринария сегодня)
A capability to adapt Schmallenberg virus to continuous cell cultures of different origin was investigated. The evidence of virus adaptation was established in continuous cell cultures BHK-21, porcine kidney, Vero, ovine kidney and Mark-145. The more efficient cell cultures were ВНК-21, PK and Vero. The aforementioned cell cultures could be of interest when choosing sensitive systems for cultivation of the agent for the purpose of receiving active virus-containing material.